Effect of post amine compound treatment on formaldehyde emission and properties of impreg - Koo, Chin Yang (2018)
The main objective of this study was to determine the effect of propylamine post-treatment on formaldehyde emission and properties of impreg sesenduk wood. Air dry strips of sesenduk wood were treated with 10%, 20%, 30% of Low molecular weight Phenol Formaldehyde and 10%, 20%, 30% of Medium molecular weight Phenol Formaldehyde using vacuum pressure treatment. After treatment, the treated wood was pre-cured in an oven at 70°C for 3 h. The samples were then cured at 150°C for 30 minutes. Post-amine treatment was carried out after the samples were taken out from oven. The spread rate were 40 g/m2, 50 g/m2 and 60 g/m2. After that, the samples were dried at room temperature and wrapped with plastic before conditioned in a conditioning room. The samples were conditioned until constant weight of the samples were achieved. The results showed that post propylamine had successfully reduced formaldehyde emission of sesenduk wood treated with low and medium molecular weight phenol formaldehyde resins. The effectiveness of the treatment dependent on the spread rate of the propylamine.